PENDEKATAN SISTEM DALAM PEMBELAJARAN - Imam Nur Hakim (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : An approach that can be used to determine the quality of the educational process is a systems approach. Through a systems approach, we can see various aspects that influence the success of a process. Learning is referred to as a system because it contained the components that are interrelated and mutually influential. Teachers, students, materials, methods, media, facilities and infrastructure are components contained in the study. Availability and effectiveness of each component will then determine the success of a lesson. Key Words: System and Learning.